Mechanisms for Protecting Government Legitimacy (A New Look) - Tariq Abdel Wahab (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The subject of the study deals with the most important mechanisms on which governments depend on establishing the pillars of political legitimacy and authority. They do not necessarily protect them from treachery or coup. The peacefulness of these mechanisms makes governments of all kinds derive from real legitimacy, apart from the fact that the means of violence and coercion used by the authorities make them legitimate.